Detection and Identification of Bartonella Species Pathogenic for Humans by PCR Amplification Targeting the Riboflavin Synthase Gene (ribC) - Johnson, G. (American Society for Microbiology, 2003)
Several Bartonella species have now been implicated as human pathogens. The recovery of these fastidious organisms in the clinical microbiology laboratory remains difficult, and current methods are still relatively insensitive. Thus, the bartonellae are good candidates for detection by PCR. We have developed a PCR assay which uses a single primer pair targeting the riboflavin synthase gene (ribC) and detected six Bartonella species that have been implicated in human disease, B. henselae, B. quintana, B. bacilliformis, B. clarridgeiae, B. elizabethae, and B. vinsonii subsp. berkhoffii. Species identification is achieved simply by restriction enzyme digestion of the amplicon. This PCR assay appears to be specific for the Bartonella genus because it failed to amplify DNA from several other bacterial species.